Optimizing the Quality of Graduates through Practices Teaching on Campus - Uyuni Widiastuti; Iskandar Muda; Adina S Sembiring (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
Music, dance and theater arts can be opportunities to get jobs in the fields of art practitioners, art entrepreneurs, event organizers, art studio managers and artists. The Department of Ballet, Faculty of Language and Arts, State University of Medan has study programs in the arts, including: Music Education Study Program, Dance Education Study Program and Performing Arts Study Program. To explore creativity and broaden students' knowledge in the arts, the Department of Sendratasik invites several practitioners in the fields of music, dance, theater whose works are well known at the national and international levels. Based on the practical implementation of teaching on campus, students are motivated and enthusiastic in participating in the learning process with practitioners.